2018
DOI: 10.1080/17453674.2018.1478570
|View full text |Cite
|
Sign up to set email alerts
|

Identification and treatment of residual and relapsed idiopathic clubfoot in 88 children

Abstract: Background and purpose — The Ponseti treatment is successful in idiopathic clubfoot. However, approximately 11–48% of all clubfeet maintain residual deformities or relapse. Early treatment, which possibly reduces the necessity for additional surgery, requires early identification of these problematic clubfeet. We identify deformities of residual/relapsed clubfeet and the treatments applied to tackle these deformities in a large tertiary clubfoot treatment center.Patients and methods — Retrospective chart revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 15 publications
0
25
0
3
Order By: Relevance
“…Finally, the scores of the areas were added, and the lower the nal score, the better the quality of life [21]. g. Recurrence was de ned as the reappearance of one to all previous deformities after successful initial treatment [4].…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the scores of the areas were added, and the lower the nal score, the better the quality of life [21]. g. Recurrence was de ned as the reappearance of one to all previous deformities after successful initial treatment [4].…”
Section: Participantsmentioning
confidence: 99%
“…Varieties of treatments are suggested for patients [7]. The standard and benchmark treatment strategy is the Ponseti method of management, which involves manipulation and weekly casting, percutaneous Achilles tenotomy in most patients, and maintenance of correction with braces for several years [4,8]. The rationale for using braces is that recurrence of clubfoot is common even after successful correction [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stouten et al reported that isolated equinus deformity accounted for 40% of all observed relapses, with a further 36% displaying some element of equinus. 20 In a study assessing correlations between foot function and perceived disability, McCahill et al found that perceived disability was associated with equinus deformity, hindfoot deformity in coronal and sagittal planes, and medial forefoot pressure gait parameters. 21 Residual or recurrent deformity of the hindfoot causes significant disability.…”
Section: Introductionmentioning
confidence: 99%
“…Early relapse is usually encountered within the first 2 years of successfully completing the Ponseti treatment [8][9][10][11][12] and responds relatively well to the repeated application of this method [9,10,13,14]. Late relapsed feet are frequently treated with various types of surgery; however, the Ponseti technique is still recommended as the first treatment irrespective of age or severity of the deformity.…”
Section: Introductionmentioning
confidence: 99%